Contributions to the botanical journal Sunyatsenia from 1930 to 1948 - Zhao, Wan-Yi; Xu, Ke-Wang; Fan, Qiang; Liao, Wen-Bo (Phytotaxa, 2016)
The botanical journal Sunyatsenia was founded by Professor Chun Woon-Young in 1930 and named in honor of Sun Yat-sen. Sunyatsenia was one of the earliest English taxonomic journals in China; it was also a truly international journal focusing on plant taxonomy, systematics and floristic phyto-geography. A great number of research papers were published in Sunyatsenia between 1930 and 1948, and the journal was praised as one of the most important botanical publications in eastern Asia. To provide botanists with a clearer understanding of the importance of Sunyatsenia, we reviewed all papers published during its 18 year lifespan. The primary findings were manifold. First, we summarize the content of the journal. Forty one researchers published 94 articles in Sunyatsenia. Fifteen new genera, 389 new species and 44 new varieties were described in Sunyatsenia. The published papers reflect the progress of research in southern China, especially Hainan Island and Southeast Asia, during the formative years of Chinese systematic botanical studies. Sunyatsenia also included a number of pioneering research papers that promoted the study of plant systematics, floristic geography, ecology and research on China’s plant resources. During its tenure, Sunyatsenia was exchanged for taxonomic literature from institutions worldwide, thereby promoting communication among botanists and helping to enhance the library of Sun Yat-sen University. Today, 199 species (included 3 varieties) of above 433 taxa still are accepted by Flora of China, and 222 species (included 38 varieties) are considered as synonyms, and other 12 species (included 3 varieties) still are considered as suspicious taxa.